2013
DOI: 10.1016/j.physletb.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of light-like Wilson loops with a self-intersection in loop space

Abstract: Recently, we proposed a general evolution equation for single quadrilateral Wilson loops on the light-cone. In the present work, we study the energy evolution of a combination of two such loops that partially overlap or have a self-intersection. We show that, for a class of geometric variations, then evolution is consistent with our previous conjecture, and we are able to handle the intricacies associated with the self-intersections and overlaps. This way, a step forward is made towards the understanding of lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The evolution of the gauge-invariant path-dependent TMDs with the light-like cusped Wilson lines can also be associated with the geometric evolution in the generalized space [189][190][191]. The differential shape variations of the underlying contours to the Wilson loops are formulated in terms of the Fréchet derivative [192,193] and the equations of motion in the loop space are dual to the energy and rapidity evolution of the TMDs having the same structure of the Wilson lines [194,195].…”
Section: Theoretical Developments and Experimental Prospectsmentioning
confidence: 99%
“…The evolution of the gauge-invariant path-dependent TMDs with the light-like cusped Wilson lines can also be associated with the geometric evolution in the generalized space [189][190][191]. The differential shape variations of the underlying contours to the Wilson loops are formulated in terms of the Fréchet derivative [192,193] and the equations of motion in the loop space are dual to the energy and rapidity evolution of the TMDs having the same structure of the Wilson lines [194,195].…”
Section: Theoretical Developments and Experimental Prospectsmentioning
confidence: 99%
“…Furthermore in [29] we demonstrated the validity, at leading order, of our conjecture for two simple extensions of our originally considered quadrilateral Wilson loops, one with overlapping segments and one with a self-intersection. Recently [30] we also demonstrated that the new derivative we introduced in [22] is a special case of the Fréchet derivative, itself having a perturbative expansion when applied to the lightlike quadrilateral supports our belief that (9) is valid for higher-orders.…”
Section: Conjectured Evolution Equationmentioning
confidence: 55%
“…They can also be related to the energy/rapidity evolution of the TMDs with pure light-like Wilson lines [21,22]. In other words, starting from a loop having a given shape, one can come to a loop with another shape by solving the above evolution equations.…”
Section: Equations Of Motion In the Loop Spacementioning
confidence: 99%
“…These differential operators in the loop space determine the evolution of the Wilson loops in the coordinate representation. They can also be related to the energy/rapidity evolution of the TMDs with pure light-like Wilson lines [22,23]. In other words, starting from a loop having a given shape, one can come to a loop with another shape by solving the above evolution equations.…”
Section: Equations Of Motion In the Loop Spacementioning
confidence: 99%